Change Detection of Benthic Habitat Communities using Landsat Imageries in Wakatobi Islands from 1990 to 2017 - Muhammad Hafizt; Novi Susetyo Adi; Pramaditya Wicaksono; Doddy Mendro Yuwono; Bayu Prayudha; Suyarso Suyarso (Faculty of Geography, Universitas Gadjah Mada, 2021)
Currently, coral reef and seagrass ecosystems in Wakatobi Islands are categorized as 'poor' because the coverage of the healthy coral is less than 50%. Therefore, detailed information about their condition through time is needed to prevent coastal degradation. Time-series analysis of Landsat images recorded in 1990, 2000, 2010, and 2017 is expected to provide information on coral reefs' habitat in Wakatobi Islands over the studied period. This study aims to determine areas that experience drastic changes in benthic habitat cover and analyze the dynamics of the changes. The image processing procedures used in this study are image correction, image classification, and applying the Change Detection Model. The image correction consists of geometric, sunglint, and water column correction, while the change detection model uses SPEAR Tools in ENVI software. The results showed a precise location that experienced a drastic change in benthic habitat cover and the changes in benthic habitat classes every ten years, which started from 1990 to 2017.